China goes global : the partial power - Shambaugh, David L. (Oxford ; New York : Oxford University Press, 2013)
"Most global citizens are well aware of the explosive growth of the Chinese economy. Indeed, China has famously become the "workshop of the world." Yet, while China watchers have shed much light on the country's internal dynamics--China's politics, its vast social changes, and its economic development--few have focused on how this increasingly powerful nation has become more active and assertive throughout the world. In China Goes Global, eminent China scholar David Shambaugh delivers the book that the world has been waiting for--a sweeping account of China's growing prominence on the international stage. Thirty years ago, China's role in global affairs beyond its immediate East Asian periphery was decidedly minor and it had little geostrategic power. As Shambaugh charts, though, China's expanding economic power has allowed it to extend its reach virtually everywhere--from mineral mines in Africa, to currency markets in the West, to oilfields in the Middle East, to agribusiness in Latin America, to the factories of East Asia. Shambaugh offers an enlightening look into the manifestations of China's global ambitions: its extensive commercial footprint, its growing military power, its increasing cultural influence or "soft power," its diplomatic activity, and its new prominence in global governance institutions. But Shambaugh is no alarmist. In this balanced and well-researched volume, he argues that China's global presence is more broad than deep and that China still lacks the influence befitting a major world power--what he terms a "partial power." He draws on his decades of China-watching and his deep knowledge of the subject, and exploits a wide variety of previously untapped sources, to shed valuable light on China's current and future roles in world affairs"--
"In China Goes Global, eminent China scholar David Shambaugh delivers the book that the world has been waiting for--a sweeping account of China's growing prominence on the international stage. Thirty years ago, China's role in global affairs beyond its immediate East Asian periphery was decidedly minor and it had little geostrategic power. As Shambaugh charts, though, China's expanding economic power has allowed it to extend its reach virtually everywhere--from mineral mines in Africa, to currency markets in the West, to oilfields in the Middle East, to agribusiness in Latin America, to the factories of East Asia. Shambaugh offers an enlightening look into the manifestations of China's global ambitions: its extensive commercial footprint, its growing military power, its increasing cultural influence or "soft power," its diplomatic activity, and its new prominence in global governance institutions. But Shambaugh is no alarmist. In this balanced and well-researched volume, he argues that China's global presence is more broad than deep and that China still lacks the influence befitting a major world power--what he terms a "partial power." "--
Machine generated contents note: -- Preface -- I. Understanding China's Global Impact -- II. China's Global Identities -- III. China's Global Diplomatic Presence -- IV. China and Global Governance -- V. China's Global Economic Presence -- VI. China's Global Cultural Presence -- VII. China's Global Security Presence -- VIII. Coping with a Globalized China -- Appendicies.
economic&political bookfair2016
Includes bibliographical references (p. 319-381) and index.
Keywords: Globalization -- China; POLITICAL SCIENCE / Globalization; HISTORY / Asia / China; China -- Foreign economic relations; China -- Economic policy -- 2000-